MODEL HUBUNGAN PENDUDUK DAN KONVERSI LAHAN DENGAN KETERSEDIAAN AIR BERSIH UNTUK PERENCANAAN PENGELOLAAN SUMBER DAYA AIR MELALUI METODE SYSTEM DYNAMICS DI KABUPATEN BEKASI - Darwati Susilastuti; I Made Putrawan; C. Hanny Wijaya (Environmental Research Center (PPLH) of Udayana University, 2009)
The objective of this research is to develop a system dynamics model that represents the relationship between population sub system and land conversion sub system with freshwater availability sub system in Bekasi Regency. The models are used to predict the relationship until 2025. The models are designed, both with and without intervention factors to population behavior toward water. The purpose of this study is to strengthen water resources management planning in Bekasi Regency. The method of the research was system dynamics. Water availability as a system was represented as a simple model in line with the factors in this research, so that the model represents the real world. The Causal Loop Diagram showed that factors in sub system and inter sub system formed balancing causal feedback loop. Model behavior simulation showed that freshwater availability (i.e. surface water and shallow ground water) decreased substantially (collapse) from 2003 until 2025. The decrease was caused by water pollution rather than the population growth and land conversion increasing. Population numbers increased slowly (growth), while land carrying capacity decreased gradually (decay). It is predicted, if the condition does not change, water crisis will happen in 2018. When community's behavior for water (i.e. thrifty and sanitation behavior) increase begin 2008, it is predicted that beginning from 2009, the freshwater availability will increase, the water crisis can be suspended, and the freshwater inventory can be reserved. Based on those findings, it could be suggested that water resources management planning should consider water as a system and integrate supply side management, demand side management, and governance side management.